2011
DOI: 10.4088/jcp.10m06443
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Serotonin-Related Gene andCOMTGene Polymorphisms With Criminal Behavior in Schizophrenic Disorder

Abstract: These results indicate that the TPH1 CC recessive genotype is likely to be a genetic risk factor for criminal behavior, especially homicidal behavior in patients with schizophrenia. However, COMT gene polymorphisms were not associated with criminal behavior in schizophrenic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Findings of the present study are consistent with some of the results of Lafuente et al, 12 who found no linkage between the À141C Ins/Del polymorphism and the catechol-O-methyltransferase polymorphism (AÀ278 G, G158A), which has been widely studied as a susceptibility gene for the risk of schizophrenia. [22][23][24][25] In view of the relatively small sample analysed in the present study, replicate studies to evaluate these possibilities are in progress.…”
Section: Discussionmentioning
confidence: 97%
“…Findings of the present study are consistent with some of the results of Lafuente et al, 12 who found no linkage between the À141C Ins/Del polymorphism and the catechol-O-methyltransferase polymorphism (AÀ278 G, G158A), which has been widely studied as a susceptibility gene for the risk of schizophrenia. [22][23][24][25] In view of the relatively small sample analysed in the present study, replicate studies to evaluate these possibilities are in progress.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have shown that low levels of serotonin are associated with both reactive and instrumental aggression [2] , [7] , [8] , [10] , [25] , [31] , [34] , [41] , [43] , [45] , [51] , [66] , [74] [78] and impulsivity. [7] , [10] , [22] , [25] , [31] , [34] , [37] , [43] , [51] , [72] , [77] , [79] In addition, low serotonin levels [31] , [55] and reduced levels of 5-hydroxyindoleacetic acid, a serotonin metabolite, have been found in aggressive or violent populations. [2] , [31] , [41] , [43] , [52] , [74] Furthermore, a negative correlation between the serotonin 5-HT1A receptor and aggressive behaviour has been established.…”
Section: Resultsmentioning
confidence: 99%
“… [6] , [17] , [41] , [61] , [66] , [75] , [101] [105] Given the influence that neurotransmitters and hormones have on aggression, a genetic basis of violence can be expected in related genes. [76] , [106] , [107] For example, the influence of serotonin transporters [18] , [41] , [108] and receptors, [61] tryptophan hydroxylase, [2] , [77] MAO-A, [83] , [106] catechol-O-methyltransferase, [18] , [77] , [89] dopamine receptors, [17] , [41] , [86] – [88] , [104] , [107] the androgen receptor [64] , [95] , [109] and the corticotrophin releasing hormone receptor [110] have been mentioned. However, in a meta-analysis including these genes, no single gene was significantly correlated with aggression.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the COMT Val158Met polymorphism had no significant effect on the presence of aggression in the Korean schizophrenia sample; however they found the Met-allele carriers to score higher in verbal aggression within the aggressive schizophrenia subgroup. Koh et al [ 49 ] examined inpatients from a forensic psychiatric hospital in Korea. When they compared the frequencies of criminal or homicidal schizophrenia patients with healthy controls, they did not find Val158Met to be associated.…”
Section: Methodsmentioning
confidence: 99%